Breeding for improved drought tolerance in Chickpea (Cicer arietinum L.). (10th April 2017) - Maqbool, Muhammad Amir; Aslam, Muhammad; Ali, Hina
Abstract: Chickpea ( Cicer arietinum L.) is an important legume crop as a protein source across the world. It is mostly grown on arid and marginal lands where it faces drought stress at different growth stages. Drought stress exerts drastic effects on nutrient uptake, hinders the nodule formation and adversely affects yield and yield components. Generally drought at any growth stage and organizational level is responsible for reduction in economic yield. Significant variability in chickpea germplasm is present on the basis of responses to drought stress in the form of drought escape, drought avoidance and drought tolerance; these mechanisms prevent chickpea crop from harmful effects of drought. Improvement in chickpea germplasm against drought stress could be made by using several breeding approaches, that is introduction, hybridization, mutation breeding, marker‐assisted breeding and omic techniques. These breeding approaches, especially marker‐assisted breeding and omics, are further strengthened with the availability of the chickpea genome sequence. This review highlighted the significance, status and advances in different breeding strategies for improvement of drought tolerance in chickpea.